Systematic evaluation of the Folin–Ciocalteu and Fast Blue BB reactions during the analysis of total phenolics in legumes, nuts and plant seeds. Issue 11 (23rd October 2020) - Pico, Joana; Pismag, Remigio Y.; Laudouze, Mallory; Martinez, Mario M.
Abstract : Solid Phase Extraction (SPE) is highly advised for the analysis of total phenolics in legumes and nuts, even using Fast Blue BB (FBBB), which in turn displayed better performance over SPE-Folin Ciocalteu (FC). Abstract : Folin–Ciocalteu and the more recent Fast Blue BB (FBBB) reactions are used for the quantification of total phenolics in food matrices. Despite its known interferences, Folin–Ciocalteu is still widely employed, considering Solid Phase Extraction (SPE) as clean-up step only in a few cases. Meanwhile, FBBB has shown no interferences for the determination of total phenolics in fruits and cereals, although its utilization in other popular matrices containing potential interferences, such as legumes, remains unexplored. In this study, the total phenolic content of 24 flours from legumes, cereals, fruits, nuts and plant seeds was evaluated by Folin–Ciocalteu and FBBB, with and without SPE. Folin–Ciocalteu showed interferences for 75% of the flours (attributed to reducing sugars and enediols), whereas FBBB only for legumes and nuts (attributed to the presence of tyrosine), both methods in those matrices requiring SPE. Although both SPE-FBBB and SPE-Folin–Ciocalteu presented excellent reproducibility, SPE-FBBB displayed 1.5 times higher sensitivity.